Risk factors for pertussis among hospitalized children in a high HIV prevalence setting, South Africa. (March 2018) - du Plessis, N.M.; Ntshoe, G.; Reubenson, G.; Kularatne, R.; Blumberg, L.; Thomas, J.; Avenant, T.
Highlights: PCR results confirmed pertussis infections in 6.2% of patients hospitalized for respiratory symptoms and signs suggestive of pertussis. Bordetella pertussis poses a greater risk to infants who are too young for the first vaccine dose. Other infants at risk are those who are not vaccinated in a timely manner, and those who do not receive all three primary doses. There was no difference in pertussis infection rate between HIV-uninfected and HIV-infected children. B. pertussis infection was unrelated to poor nutritional status. Abstract: Background: In low- and middle-income countries, including South Africa, the epidemiology of pertussis in relation to immunization, nutritional, and HIV status is poorly described. This article reports on risk factors in South African children hospitalized with pertussis. Methods: A prospective, hospital-based, sentinel surveillance programme for pertussis was conducted in Gauteng Province, South Africa. Hospitalized children (≤10 years) meeting the surveillance criteria for clinically suspected pertussis were screened and enrolled. Nasopharyngeal specimens were collected for real-time multiplex PCR and culture of Bordetella species. Results: Bordetella pertussis was detected in 6.2% (61/992) of children. Pertussis was significantly more prevalent in infants younger than 3 months (9.8%; 38/392) and in young children between the ages of 5 and 9 years (12%; 4/34) ( p = 0.0013). Of the 61 confirmed pertussis cases, 17 were too young for vaccination. Of the remaining 44 infants, vaccination DTP1 was administered in 73% (32/44) of pertussis-confirmed patients who were eligible, DTP2 in 50% (16/32), DTP3 in 54% (14/26), and DTP4 in 56% (5/9) of vaccine-eligible cases at 18 months of age. B. pertussis infection was less likely in children immunized at least once (5%, 32/692) than in unvaccinated children (10%, 24/230) ( p = 0.0001). HIV exposure and infection status were determined in 978 (99%) patients: 69% (678/978) were HIV-unexposed and uninfected and 31% (300/978) were HIV-exposed. Of these HIV-exposed patients, 218 (22%) were proven HIV-exposed and uninfected and 82 patients were HIV-infected (8.4%, 82/978). HIV prevalence was similar in pertussis-positive (6%, 5/82) and pertussis-negative (6%, 55/896) children ( p = 0.90). B. pertussis infection was unrelated to poor nutritional status. Conclusions: In South Africa, B. pertussis poses a greater risk to infants who are too young for the first vaccine dose, those who are not vaccinated in a timely manner, and those who do not receive all three primary doses. HIV infection and HIV exposure were not associated with pertussis infection.